Dual PI3 K/mTOR inhibition reduces prostate cancer bone engraftment altering tumor-induced bone remodeling - Andrea Mancini; Alessandro Colapietro; Simona Pompili; Andrea Del Fattore; Simona Delle Monache; Leda Assunta Biordi; Adriano Angelucci; Vincenzo Mattei; Chris Liang; Giovanni Luca Gravina; Claudio Festuccia (Tumor Biology)
Morbidity in advanced prostate cancer patients is largely associated with bone metastatic events. The development of novel therapeutic strategies is imperative in order to effectively treat this incurable stage of the malignancy. In this context, Akt signaling pathway represents a promising therapeutic target able to counteract biochemical recurrence and metastatic progression in prostate cancer. We explored the therapeutic potential of a novel dual PI3 K/mTOR inhibitor, X480, to inhibit tumor growth and bone colonization using different in vivo prostate cancer models including the subcutaneous injection of aggressive and bone metastatic (PC3) and non-bone metastatic (22rv1) cell lines and preclinical models known to generate bone lesions. We observed that X480 both inhibited the primary growth of subcutaneous tumors generated by PC3 and 22rv1 cells and reduced bone spreading of PCb2, a high osteotropic PC3 cell derivative. In metastatic bone, X480 inhibited significantly the growth and osteolytic activity of PC3 cells as observed by intratibial injection model. X480 also increased the bone disease-free survival compared to untreated animals. In vitro experiments demonstrated that X480 was effective in counteracting osteoclastogenesis whereas it stimulated osteoblast activity. Our report provides novel information on the potential activity of PI3 K/Akt inhibitors on the formation and progression of prostate cancer bone metastases and supports a biological rationale for the use of these inhibitors in castrate-resistant prostate cancer patients at high risk of developing clinically evident bone lesions.